The public debt as handicap to economic growth - Teixeira, N.; Luz, R.; Silva, R. V. da.; Pereira, L.; Silva, S. V. da. (International Journal of Public Law and Policy, 2024)
The impact that public debt has on economic growth is increasingly a topic of interest and it has been since the most recent economic and financial crisis of 2008 that it has come to occupy a prominent place in the literature. In this context, it becomes extremely important to understand the impact that the increase in public debt has on the growth of economies. Thus, the purpose of this research paper is to assess the effect that debt may have on the economic growth of countries. We analyse the relation in three countries: Estonia, Greece and Portugal. Our findings suggest that the public debt of these countries do not directly affect the growth.